LGBT self-identity management on Instagram - Wahyu Abadi, Totok; Dewi, Novita Purnama; Febriana, Poppy Febriana; Asy'ari, Nur Aini Shofiya; Nygymanova, Nurbany (Jurnal Studi Komunikasi, 2025)
To express their identity on social media, the LGBT community needs to manage their self-presentation so that it can be accepted by the wider community. Building on this, the study aims to explain how LGBT individuals manage their identities through social media and the challenges they have encountered. This study employed a qualitative method by analysing four (4) Instagram accounts of LGBT members as data sources. The Instagram accounts are the following: @mimi. peri, @joviadhiguna, @lucintaluna_manjalita, and @ablaolevera which were chosen based on previously determined criteria through purposive sampling techniques. The units of analysis used are phrases, clauses, sentences and images in Instagram accounts that have been compared with identity management theory, CMC and queer theory. The results of the study show that LGBT individuals in representing their identity are more open through Instagram accounts to build interpersonal communication with fellow LGBT, making them feel safe, comfortable and can be accepted by other groups. Second, LGBT individuals are representing their new identity in the form of fashion clothing, body gestures, and makeup. Third, there is a renegotiation of the face for LGBT individuals in representing their identity on Instagram media. The novelty in this study is that face renegotiation can enhance the development of interpersonal relationships on social media. Self-identity management can be done through the exploration, struggle, and renegotiation phases.